DEVELOPMENT OF CALCULATION TOOL FOR RESPIRATORY TRACT DEPOSITION DEPENDING ON AEROSOLS PARTICLE DISTRIBUTION. Issue 3 (26th April 2019) - Iwaoka, Kazuki; Hosoda, Masahiro; Tokonami, Shinji; Enriquez, Eliza B; Palad, Lorna Jean H; Kanda, Reiko
Abstract: Inhalation exposures occur by inhaled radioactive nuclides depositing in the various locations in the respiratory tract (International Commission on Radiological Protection Publication 66). Respiratory tract deposition depends on particle size. The sensitivity to ionising radiation is different among respiratory regions. Under actual atmospheric environments, the radionuclides attach to aerosols of various size in the atmosphere, so the particle size of radionuclides changes differently. Therefore, it is important for the estimation of health impact to calculate the respiratory tract deposition under atmospheric environment wherein the various sizes of radioactive nuclides (i.e. polydisperse particles) exists. In this study, a tool which can calculate the respiratory tract deposition on the basis of polydisperse particle size distribution was developed to estimate dose depending on variable aerosol particle sizes.